Handbook of Liquid Crystals 1998
DOI: 10.1002/9783527620623.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Features

Abstract: General Structural Features' In this contribution the nomenclature D for a columnar mesophase of disk-like molecules has been used, but the reader should appreciate that D,, D,, D, etc. are the same as Col,, Col,, Colt etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 217 publications
1
37
0
Order By: Relevance
“…19 Supra-molecular discotic mesophase structures driven by molecular recognition processes through non-covalent interactions have become an interesting research topic and a promising approach for practical applications and scientific challenges. 20,21 Non-covalent interactions include hydrogen (H)-bonding, electrostatic (ion-ion, ion-dipole, and dipoledipole) interactions, p-p stacking interactions, van der Waals interactions, and hydrophobic-hydrophilic effects along with others. [22][23][24][25][26][27][28][29][30][31] Since Lehn first discovered H-bonding induced supra-molecular LC phases, H-bonding has become a topic of major research due to its moderate bonding energy, directionality, selectivity and reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…19 Supra-molecular discotic mesophase structures driven by molecular recognition processes through non-covalent interactions have become an interesting research topic and a promising approach for practical applications and scientific challenges. 20,21 Non-covalent interactions include hydrogen (H)-bonding, electrostatic (ion-ion, ion-dipole, and dipoledipole) interactions, p-p stacking interactions, van der Waals interactions, and hydrophobic-hydrophilic effects along with others. [22][23][24][25][26][27][28][29][30][31] Since Lehn first discovered H-bonding induced supra-molecular LC phases, H-bonding has become a topic of major research due to its moderate bonding energy, directionality, selectivity and reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, thermotropic hexagonal columnar phases are formed by anisometric disclike molecules [23] or by amphiphilic or polymeric tapershaped molecules.…”
Section: Pentaerythritol Tetrakis(34-dialkoxybenzoates)mentioning
confidence: 99%
“…1- 18 On the other hand, gold nanorods (GNRs) have been extensively studied for their anisotropic properties and their applications not only in materials science but also in biosciences have been sought. 19,20 Here it is shown that GNRs can be easily inserted into the supramolecular order of DLCs without disturbing their mesomorphism.…”
mentioning
confidence: 99%